PENGEMBANGAN KEPRIBADIAN GURU DALAM PERSPEKTIF PENDIDIKAN ISLAM: SYSTEMATIC LITERATURE REVIEW - Annanda Muhammad Rizky Ramadhani; Nabila Aulia Rahmah; Mursidin; Ayi Muammar (CV. ADIBA AISHA AMIRA, 2026)
Teacher personality represents a strategic factor in educational success, particularly within Islamic Religious Education (PAI) that emphasizes balance across cognitive, affective, and psychomotor dimensions. This study aims to comprehensively analyze concepts, characteristics, strategies, and implications of teacher personality development from an Islamic education perspective through a Systematic Literature Review (SLR). Data sources comprise ten nationally published scientific journal articles from 2015–2024, selected through identification, screening, eligibility, and inclusion stages. Analysis employed comparative analysis and thematic synthesis. Findings reveal that teacher personality in Islamic education constitutes a multidimensional construct encompassing moral dimension (akhlak) as value foundation, spiritual dimension as self-awareness reinforcement, and professional dimension as pedagogical implementation. However, fragmentation persists between normative-religious and empirical scholarship, alongside insufficient attention to integrating personality values with digital era challenges. This study proposes an integrative and contextual teacher personality development model addressing identified gaps. These findings are expected to contribute theoretically to Islamic education scholarship and serve as foundation for formulating more comprehensive and relevant teacher personality development models.